Worm burden and immunological responses in Corriedale and Crioula Lanada sheep following natural infection with Haemonchus contortus - Bricarello, P. A.; Gennari, S. M.; Oliveira-Sequeira, TCG; Vaz, CMSL; de Goncalves, I. G.; Echevarria, FAM (Elsevier B.V., 2004)
The effects of natural infection with Haemonchus contortus were compared in 15 Corriedale lambs and 18 Crioula Lanada lambs kept in the grazing conditions after weaning. The following parameters were assessed weekly for 9 consecutive weeks: number of eggs per gram of feces (EPG), packed cell volume (PCV), total serum proteins (TSP) and albumin (ALB). At 10 weeks, the animals were slaughtered and autopsied to evaluate to the worm burden and eosinophil, mast cell and globule leukocyte counts in histological sections of the abomasum. EPG counts and worm burden were significantly lower in Crioula lambs, which also showed higher levels of PCV, TSP and ALB, as well as higher eosinophil and globule leukocyte counts. Mast cell counts were similar for the two breeds. These results indicate that, under intensive pasture conditions, the Crioula Lanada breed shows a better response to natural infection with H. contortus, suggesting greater resistance to parasitism. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: sheep; Haemonchus contortus; breed; corriedale; Crioula Lanada